PENGARUH SRATEGI DRTA (DIRECTED READING THINKING ACTIVITY) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SD MUHAMMADIYAH 6 PEKANBARU - Misriati '; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a quasi experimental with nonequivalent control group designs which is backed by the low ability of student’s reading comprehension skills in elementary school. The research was conducted at SD Muhammadiyah 6 Pekanbaru in the even semester of the academic year 2016/2017. The purpose of this study was to determine the effect of DRTA strategy (Directed Reading Thinking Activity) toward student’s reading comprehension skills in class V SD Muhammadiyah 6 Pekanbaru. The subject of this study was student in class V which is VA as controlled class and VB as experimental class which is consist of 19 student each class. The stages of this research is to conduct the pretest, followed by applying DRTA strategy (Directed Reading Thinking Activity) in experiment class and lecture method in control class. Next, a postest is conducted in both classes. The results showed that in the experimental class there was a difference in the ability to increase from the average pretest score of 65,895 to 83,158 in the postest with the average gain of 0,55 medium category. While the control class is also an increase in average of 67,158 to 73,684 in the postest with an average gain of 0.20 low category. In this study, the DRTA strategy (Directed Reading Thinking Activity) gives a learning skill of 74.7% while 25.7% of student’s reading comprehension skills are caused by other factors. Influence given with very strong relationship level with a correlation coefficient of 0.862.Keywords: DRTA strategy (Directed Reading Thinking Activity), reading comprehension skills